Failure of B Cell Tolerance in CVID - Richardson, Christopher T.; Slack, Maria A.; Dhillon, Gitika; Marcus, Carolina Z.; Barnard, Jennifer; Palanichamy, Arumugam; Sanz, Ignacio; Looney, Richard John; Anolik, Jennifer H. (Frontiers in Immunology, 2019)
Common variable immunodeficiency (CVID) comprises a group of related disorders defined by defects in B cell function and antibody production. Concurrent autoimmune features are common, but the underlying pathogenic mechanisms of autoimmunity in CVID are poorly understood. Overlap in some clinical and laboratory features suggests a shared pathogenesis, at least in part, with systemic lupus erythematosus (SLE). One important part of SLE pathogenesis is loss of B cell tolerance, an aspect that warrants further study in CVID. The study of inherently autoreactive 9G4+ B cells has led to a greater understanding of B cell tolerance defects in lupus. Study of these B cells in CVID has yielded conflicting results, largely due to differences in methodological approaches. In this study, we take a comprehensive look at 9G4+ B cells throughout B cell development in CVID patients and compare patients both with and without autoimmune features. Using flow cytometry to examine B cell subpopulations in detail, we show that only those CVID patients with autoimmune features demonstrate significant expansion of 9G4+ B cells, both in naïve and multiple memory populations. Examination of two autoreactive B cell subsets recently characterized in SLE, the activated naïve (aNAV) and double negative 2 (DN2) B cells, reveals an expanded 9G4+ DN2 population to be common among CVID patients. These results reveal that both multiple central and peripheral B cell tolerance defects are related to autoimmunity in CVID. Furthermore, these data suggest that the autoreactive DN2 B cell population, which has not previously been examined in CVID, may play an important role in the development of autoimmunity in patients with CVID.